Mortality and Its Predictors among Adult Human Immune-Deficiency Virus-Infected Patients Attending Their Antiretroviral Treatment at Health Centers, Addis Ababa, Ethiopia: Multicenter Retrospective Cohort Study - Selam Tesfayohannes; Sisay Shine; Abinet Mekuria; Sisay Moges (AIDS Research and Treatment)
Introduction. In resource-limited settings such as Ethiopia, where the prevalence of HIV/AIDS is high, a number of factors, including economic, demographic, behavioral risk, and health factors, affect how long people with AIDS are treated with antiretroviral therapy. Since several aspects of the clinical setup may have an impact on ART patients’ survival, this study was conducted in health centers. Determining the mortality rate and survival factors among adult HIV-infected patients receiving ART at health centers in Addis Abeba’s Kirkos subcity is the primary goal of this study. Methods. A retrospective cohort study was carried out at the health center in Addis Abeba’s Kirkos subcity. The source population consisted of all adult HIV-positive patients who were being followed up between December 1, 2014, and October 30, 2019. A total of 665 samples were collected using a computer-generated simple random sampling method in each of the three health centers that were chosen by a lottery system depending on the number of patients in the follow-up. Trained data collectors took the information out of the patient card and the electronic database. Regressions using the Kaplan‐Meier and Cox proportional hazards were employed. Results. The incidence of death rate in adult HIV-positive patients was 55 (8.5%) fatalities, translating to a death rate of 3.25 per 100 person-years. The majority of deaths occurred within 6 months of ART initiation. Predictors of mortality were: age above 50 years (AHR = 4.90, 95% CI: 2.00, 11.98), tuberculosis comorbidity (AHR = 3.46, 95% CI: 1.23, 3.33), lack of drug adherence (AHR = 1.76, 95% CI: 1.23, 3.33), co-trimoxazole therapy (AHR = 2.59, 95% CI: 1.37, 4.90), and CD4 cell count less than 200/dl (AHR = 2.77, 95% CI: 1.30, 5.92). Conclusion and Recommendation. Adult HIV-positive individuals had an incidence of the death rate of 55 (8.5%), which equates to 3.25 deaths per 100 person-years. Age category over 50, TB comorbidity, WHO stage IV, lack of medication adherence, co-trimoxazole therapy, body mass index under 18.5 kg/m2, and CD4 cell count under 200/dl were predictors of mortality. Therefore, it is important to focus on prevention, early identification, and treatment of HIV/AIDS for these predictors at all levels of the HIV/AIDS chronic care package in order to increase survival.